Body mass index and vigorous physical activity in children and adolescents: an international cross-sectional study. - Braithwaite, Irene E (2017)
Aim: To examine the relationship between reported vigorous physical activity (VPA) and body mass index (BMI) in children (6–7 years) and adolescents (13–14 years). Methods: In the International Study of Asthma and Allergies in Childhood Phase Three, 75 895 children's parents and 199 502 adolescents answered questions relating to VPA, height and weight. The association between VPA and BMI was analysed using general linear models, adjusting for country gross national index. Results: Compared to children who undertook no VPA, those in the infrequent group (once or twice per week) and those in the frequent group (three or more times per week) had mean (95% CI) BMI values 0.07 kg/m 2 (0.03–0.11) and 0.09 kg/m 2 (0.03–0.15) greater, respectively (p = 0.001). Compared to adolescents reporting no VPA, those in the infrequent group had a BMI 0.19 kg/m 2 (0.15–0.23) greater while those in the frequent group had a BMI 0.01 kg/m 2 (−0.03–0.05) greater (p < 0.0001). Conclusion: Reported VPA is not associated with lower BMI among children and adolescents. Investigation of VPA and BMI may be best undertaken in conjunction with other variables in the energy expenditure equation. A focus on VPA alone may be an inefficient way to manage BMI.